Perbandingan Diplomasi Kopi Indonesia Di Qatar, Selandia Baru Dan Jepang Pada Masa Pemerintahan Jokowi - Rakhmadi, Roby (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
This study discusses the comparison of Indonesian coffee diplomacy in Qatar, New Zealand, and Japan during the administration of President Joko Widodo (Jokowi). Coffee diplomacy is part of Indonesia's soft power to expand the market and strengthen diplomatic relations through its leading commodity, namely coffee. This study aims to analyze the coffee diplomacy strategy in the three countries with a focus on the success of market penetration, government involvement in promotion, and local market response to Indonesian coffee. The research methods used are literature study and secondary data analysis from trade reports and interviews with coffee industry players. The results of the study show that in Qatar, coffee diplomacy is focused on introducing premium coffee through international events such as the World Expo. In New Zealand, diplomacy emphasizes business cooperation between local and Indonesian coffee entrepreneurs. Meanwhile, in Japan, the coffee diplomacy strategy focuses on sustainable marketing by utilizing cultural proximity and the rapidly growing trend of coffee consumption. These findings show that although each country has a different approach, Indonesian coffee diplomacy has succeeded in increasing the exposure of national coffee in the international market. However, challenges related to sustainability and consistency still need to be considered for long-term success.